2018
DOI: 10.1186/s13287-018-1058-z
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of bFGF and selenium on expansion and paracrine action of human amniotic fluid-derived mesenchymal stem cells

Abstract: BackgroundMesenchymal stem cell-derived conditioned medium (MSC-CM) has emerged as a promising cell-free tool for restoring degenerative diseases and treating traumatic injuries. The present study describes the effect of selenium as a reactive oxygen species (ROS) scavenger and its additive effect with basic fibroblast growth factor (bFGF) on in vitro expansion of amniotic fluid (AF)-MSCs and the paracrine actions of AF-MSC-CM as well as the associated cellular and molecular mechanisms.MethodsIn this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…The GPx activity in maternal and cord plasma as well as placental tissue was shown to be lower in pre-eclamptic pregnancies [ 15 , 30 , 46 , 49 ]. As previously described, amniotic fluid represents an important material for understanding the biological effects of Se [ 35 , 37 ]. Roy et al reported Se levels in amniotic fluid samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GPx activity in maternal and cord plasma as well as placental tissue was shown to be lower in pre-eclamptic pregnancies [ 15 , 30 , 46 , 49 ]. As previously described, amniotic fluid represents an important material for understanding the biological effects of Se [ 35 , 37 ]. Roy et al reported Se levels in amniotic fluid samples.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that ROS impacts cellular senescence and that this process is mediated by antioxidants such as glutathione, ascorbic acid, and ROS connected enzymes. Thus, by reducing ROS levels, one could improve DNA damage, prevent apoptosis, and recover mitochondrial dysfunction [ 37 ]. Therefore, in order to better understand the biological background Se has on growth amniotic fluid, it is an important biological material to study.…”
Section: Introductionmentioning
confidence: 99%
“…AF-MSCs were obtained by amniocentesis performed for fetal karyotyping between 16 and 20 weeks of gestation. AF-MSCs, previously characterized as MSCs by verification of their differentiation, proliferation, and immunological phenotypes 17 , were used in this study. All experiments were performed in triplicate on independently isolated AF-MSCs.…”
Section: Methodsmentioning
confidence: 99%
“…Differentiation of MSCs was performed as previously described 17 . Briefly, 3 × 10 4 MSCs/well were seeded in 6-well culture dishes and cultured in proliferation media to reach 100% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation